Modulation of Fibrinolytic and Gelatinolytic Activity during Adipose Tissue Development in a Mouse Model of Nutritionally Induced Obesity - Lijnen, H. Roger; Maquoi, Erik; Demeulemeester, Diego; Van Hoef, Berthe; Collen, Désiré (Thrombosis and Haemostasis, 2002)
A nutritionally induced obesity model was used to investigate the modulation of fibrinolytic and gelatinolytic activity during the development of adipose tissue.Five week old male mice were fed a standard fat diet (SFD, 13% kcal as fat) or a high fat diet (HFD, 42% kcal as fat) for up to 15 weeks. The HFD resulted in body weights of 31 ± 0.9 g, 38 ± 2.0 g and 47 ± 1.9 g at 5, 10 and 15 weeks, respectively; corresponding values for mice on the SFD were 26 ± 0.6 g, 31 ± 0.9 g and 31 ± 1.2 g (all p < 0.001). The weight of the isolated subcutaneous (SC) or gonadal (GON) fat after 15 weeks of HFD was 1,870 ± 180 mg or 1,470 ± 160 mg, as compared to 250 ± 58 mg or 350 ± 71 mg for the SFD (p < 0.001). The HFD induced marked time-dependent hyperglycemia and elevated levels of triglycerides and total cholesterol. The HFD diet also induced a marked hypertrophy of the adipocytes as compared to the SFD, e.g. diameter of 83 ± 3.0 µm versus 52 ± 4.2 µm for GON adipocytes at 15 weeks (p < 0.005). Plasma plasminogen activator inhibitor-1 (PAI-1) levels were higher in mice on the HFD as compared to the SFD; they were comparable in extracts of SC or GON adipose tissue, whereas at different time points tissue-type (t-PA) and urokinase-type (u-PA) plasminogen activator activity was somewhat lower in the adipose tissues of mice on HFD. Gelatinolytic activity (mainly MMP-2) was detected in SC but not in GON adipose tissue of mice on SFD, and decreased on the HFD. In situ zymography on cryosections did not reveal different fibrinolytic activities in SC or GON adipose tissues of the HFD as compared to the SFD groups, whereas significantly lower gelatinolytic and higher caseinolytic activities were detected in SC and GON tissues of mice on the HFD (p ≤ 0.05). The fibrillar collagen content was lower in adipose tissue of mice on HFD. Thus, in this model time-dependent development of adipose tissue appears to be associated with modulation of proteolytic activity.
Keywords: Obesity; adipose tissue; fibrinolysis; gelatinase